Sosialisasi Pendidikan Kebencanaan Pada Peserta Didik Santri Dayah Tahfidz Annisa Kabupaten Aceh Barat - Astiah Amir; Veranita Veranita; Joli Supardi; Rita Fazlina; Fadli Idris (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2022)
Socializing disaster education in schools is crucial to prevent and reducing disaster risk. Not only need to be delivered to formal education and non-formal educational institutions. This is in line with the Regulation of the Head of the National Disaster Management Agency No. 4 of 2012 concerning the Implementation of Disaster Safe Schools/Madrasahs. One of them is education in Dayah Tahfiz Annisa. In Dayah Tahfidz, Annisa consists of students for elementary to high school children. The students in Dayah still do not understand the science of disaster education. The methods used in disaster education learning are ICT, Example Non Example, and Question & Answer. The result is that the students have increased knowledge of disaster response, awareness, and resilience. Socialization about disaster education that is adapted to the content of boarding schools. So far, the students in Dayah still do not understand the science of disaster education. The methods used in disaster education learning are ICT, Example Non-Example, and Q&A. the result is that the students have increased knowledge of disaster response, disaster awareness, and disaster resilience.